2020
DOI: 10.1155/2020/2134647
|View full text |Cite
|
Sign up to set email alerts
|

After Treatment Decrease of Bone Marrow Tregs and Outcome in Younger Patients with Newly Diagnosed Acute Myeloid Leukemia

Abstract: An emerging body of evidence demonstrates that defects in antileukemic effector cells in patients with acute myeloid leukemia (AML) can contribute to the development and/or persistence of the disease. In particular, immune suppressive regulatory T cells (Tregs) may contribute to this defective antileukemic immune response, being recruited by bone marrow leukemic cells to evade immune surveillance. We evaluated Tregs (CD4+/CD45RA-/CD25high/CD127low), performing multiparametric flow cytometry on freshly collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Amount of regulatory T cells (Treg) has decreased in BM of AML patients who responded to chemotherapy, but failed to decrease in non-responding patients [ 217 ]. Also combined treatment with chemotherapy and histone deacetylase (HDAC) inhibitor panobinostat led to decreased number of TNFR2+ Treg in blood and BM of AML patients [ 218 ].…”
Section: Immune Response Recovery After Therapy In Myeloid Leukemimentioning
confidence: 99%
“…Amount of regulatory T cells (Treg) has decreased in BM of AML patients who responded to chemotherapy, but failed to decrease in non-responding patients [ 217 ]. Also combined treatment with chemotherapy and histone deacetylase (HDAC) inhibitor panobinostat led to decreased number of TNFR2+ Treg in blood and BM of AML patients [ 218 ].…”
Section: Immune Response Recovery After Therapy In Myeloid Leukemimentioning
confidence: 99%
“…As a type of immunosuppressive cells, high expression of Tregs cells has been shown to result in the escape of tumor cells [ 29 , 30 ]. Studies have reported that the expression of Tregs cells is higher in acute myeloid leukemia (AML) patients compared to healthy individuals [ 31 ], and that Tregs contribute to immune escape through the suppression of anti-leukemia treatment [ 32 ]. Macrophages, as a component of immune cells, play a crucial role in the inflammatory and tumor microenvironment [ 33 ], and are often implicated in the establishment of a microenvironment that is favorable to tumor progression through various mechanisms [ 34 ].…”
Section: Discussionmentioning
confidence: 99%